A latent class exploration of adolescent recovery capital. Issue 4 (24th January 2018) - Hennessy, Emily Alden
Abstract: Recovery capital, an ecological model, has been primarily used to study substance use disorder recovery among adults; however, as adolescents comprised 5.1% of substance treatment admissions in 2015 (Substance Abuse and Mental Health Administration, 2016), it is worth empirically exploring this model with specific attention to this population. Conditional latent variable mixture model analysis using the 2012 National Survey on Drug Use and Health explored whether there were observable classes of recovery capital among adolescents who needed treatment ( N = 1, 171) and whether sex, race, age, and history of substance use treatment differentiated class membership. The analysis revealed a 5‐class model of recovery capital classes: resource‐wealthy; strong social, weak community; religious, resource‐poor; strong community; secular, weak community. The religious, resource‐poor class was more likely to be a minority than all other classes and to be older. There were 5 qualitatively distinct patterns of recovery capital among adolescents, including a group who may be particularly vulnerable to relapse given their few capital resources.